Maternal characteristics and stunting in children aged 24–60 months in West Jawa, Indonesia: A retrospective study - Nintyas, Felantina Restyar; Komariah, Maria; Sukmawati, Sukmawati; Rahayuwati, Laili; Mirwanti, Ristina; Eriyani, Theresia (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2024)
Background: Stunting is a nutritional health problem that can have both short and long-term adverse effects on children and will ultimately lead to a decrease in human resources.Purpose: To determine the relationship between maternal characteristics and the incidence of stunting in children aged 24-60 months in Sukamulya Village.Method: Quantitative research with a case-control approach. The sample in this study amounted to 93 respondents. Data analysis that will be used in this study is univariate and bivariate analysis using Chi-square Results: The results of the bivariate statistical test showed that there was a relationship between maternal height (p-value=0.000) and maternal age at pregnancy (p-value= 0.000) on stunting of toddlers aged 24-60 months in Sukamulya Village The results of bivariate statistical tests showed there was no relationship between birth spacing (p-value=0.147) to stunting of toddlers aged 24-60 months in Sukamulya Village.Conclusion: Factors associated with the incidence of stunting are maternal height and age at pregnancy and factors that are not associated with the incidence of toddler stunting are birth spacing.